2012
DOI: 10.3389/fmicb.2012.00271
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Nitrification at Low Temperature with Zeolite in a Mining Operations Retention Pond

Abstract: Ammonium nitrate explosives are used in mining operations at Diavik Diamond Mines Inc. in the Northwest Territories, Canada. Residual nitrogen is washed into the mine pit and piped to a nearby retention pond where its removal is accomplished by microbial activity prior to a final water treatment step and release into the sub-Arctic lake, Lac de Gras. Microbial removal of ammonium in the retention pond is rapid during the brief ice-free summer, but often slows under ice cover that persists up to 9 months of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Additionally, Avrahami et al [88] found a correlation between low temperature and the occurrence of Nitrosospira. In a cold mining operation retention pond in the Northwest Territories, Canada, Nitrosospira was identified as the main AOB [89]. In addition, Hayashi et al [24] detected AOB belonging to the genus Nitrosospira in Svalbard; however, cold bioreactors treated with inorganic mine waters contained Nitrosospira together with Nitrosomonas [90].…”
Section: Nitrosospira: the Primary Enriched Aob Representativementioning
confidence: 99%
“…Additionally, Avrahami et al [88] found a correlation between low temperature and the occurrence of Nitrosospira. In a cold mining operation retention pond in the Northwest Territories, Canada, Nitrosospira was identified as the main AOB [89]. In addition, Hayashi et al [24] detected AOB belonging to the genus Nitrosospira in Svalbard; however, cold bioreactors treated with inorganic mine waters contained Nitrosospira together with Nitrosomonas [90].…”
Section: Nitrosospira: the Primary Enriched Aob Representativementioning
confidence: 99%
“…While zeolite has poor phosphate adsorption capacity, because the cavities in this highly porous material are negatively charged, the negative charge improves their adsorption capacity for ammonium and metal ions (Lin et al, 2011; Wen et al, 2016). Zeolites may also promote nitrification (Miazga‐Rodriguez et al, 2012). Each of these methods has its own specifics that must be considered.…”
Section: Assessing the Sustainability Of In‐lake Measuresmentioning
confidence: 99%
“…The ability for microbial biofilms to offer protection from environmental and predatory stress has been well documented (Aqeel et al, 2019;Lee et al, 2014;Wang et al, 2018;Wucher et al, 2021;Yin et al, 2019). For example, a common method to improve the performance of nitrification systems experiencing low temperatures or high ammonia loading is to increase the retention of biofilm biomass through the addition of carrier materials with ample surface area for microbial attachment (Aqeel and Liss, 2020;Delatolla et al, 2012;Miazga-Rodriguez et al, 2012). However, it is currently unclear whether the use of fixed-films systems can also help to overcome the low pH stress brought on by depletion of the available alkalinity, or any associated inorganic carbon limitation.…”
Section: Introductionmentioning
confidence: 99%